Policy experimentation, redistribution and voting rules - Vincent Anesi; T. Renee Bowen (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2018)
We study conditions under which optimal policy experimentation can be implemented by a committee. We consider a dynamic bargaining game in which committee members choose to implement either a risky reform or a safe alternative with known returns each period. We find that when no redistribution is allowed the unique equilibrium outcome is generically inefficient. When committee members are allowed to redistribute resources (even arbitrarily small amounts), there always exists an equilibrium that supports optimal experimentation for any voting rule with no veto players. With veto players, however, optimal policy experimentation is possible only with a sufficient amount of redistribution. We conclude that veto rights are more of an obstacle to optimal policy experimentation than constraints on redistribution.
Keywords: 330